The night is for hunting - Marsden, John, 1950- (London : Quercus, 2013)
While trying to care for a group of abandoned young children, five Australian teenagers continue their struggle for survival and their resistance against the enemy invading their homeland.
Young Adult.
Young Adult
Keywords: Survival -- Fiction; War -- Fiction; Survival after airplane accidents, shipwrecks, etc. -- Fiction; War stories; Australia -- Fiction; Australia -- Fiction